2001
DOI: 10.1177/096739110100900101
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Chlorine Depletion of Antioxidants in Polyethylene

Abstract: For many polyethylene products, their working life-span depends on retention by the material of its antioxidant. In dry air, when the working and environmental stresses remain within defined limits, the life-span of the material can be many decades. Immersed in water, for example, the diffusion and loss of antioxidant from the material's surface can increase. Also, some types of aggressive agents, if in the water, can enter the material's surface and migrate into the material to increase the depletion of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…1, it can be concluded that oxidation is initiated by radical species coming mainly from ClOH, the eventual contribution of Cl 2 being clearly insufficient to be detectable. In addition, based on the mechanisms proposed in the literature [18,20,27,32,33], it can be concluded that these radicals are formed according to scenario S3.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…1, it can be concluded that oxidation is initiated by radical species coming mainly from ClOH, the eventual contribution of Cl 2 being clearly insufficient to be detectable. In addition, based on the mechanisms proposed in the literature [18,20,27,32,33], it can be concluded that these radicals are formed according to scenario S3.…”
Section: Resultsmentioning
confidence: 84%
“…On the contrary, for other authors [18,20,32,33], Cl 2 and ClOH could directly dissociate into Cl% and HO% radicals (presumably within the PE matrix) because Cl−Cl and Cl−O bonds are characterized by a very low dissociation energy (of respectively 242 and 247 kJ mol …”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Another problem with reported ageing studies is the magnitude of free available chlorine concentrations examined and the omission of initial and/or final free available chlorine concentration. For example, Dear and Mason [7,11] found drastic differences between polyethylene pipe failure and antioxidant profiles when aging was conducted at 80 C with 0-5000 ppm versus 15,000-125,000 ppm chlorine solutions, whereby uniform antioxidant reduction and slow crack growth through the pipe wall were observed at lower chlorine levels only. Unfortunately, data were not provided to describe solution chemistry during or at the completion of the ageing process.…”
Section: Introductionmentioning
confidence: 95%
“…Chemical interaction can be examined by immersing polymer samples in neat contaminant solution [67][68][69] or by exposing them to dilute aqueous solutions [70][71][72][73]. Most accelerated ageing techniques [7,9,11,14,16,17,22,25,43] Source: Dietrich and WheltonÓ2008 Awwa Research Foundation. Reprinted with Permission.…”
Section: Introductionmentioning
confidence: 99%